1994
DOI: 10.1007/bf00262762
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dysphagia in children with cerebral palsy

Abstract: Videofluoroscopic modified barium swallow (VMBS) examinations may provide clinically relevant information regarding deglutition in children with cerebral palsy and dysphagia. A retrospective review of clinical evaluations and VMBS studies on 90 consecutive children with cerebral palsy and dysphagia was completed. Most children were referred because of concerns regarding airway protection during oral feedings. Most children had multiple disabilities and 93% were nonambulatory. The majority of children were tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
2
26

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 12 publications
1
101
2
26
Order By: Relevance
“…Estimates of frequency of aspiration in this population range from 31 to 97% (Gisel and Patrick 1988, Mirrett et al 1994, Rogers et al 1994, Wright et al 1996, whereas gastro-oesophageal reflux is reported in 32 to 75% (Abrahams and Burkitt 1970, Reyes et al 1993, Gustafsson and Tibbling 1994.…”
mentioning
confidence: 83%
“…Estimates of frequency of aspiration in this population range from 31 to 97% (Gisel and Patrick 1988, Mirrett et al 1994, Rogers et al 1994, Wright et al 1996, whereas gastro-oesophageal reflux is reported in 32 to 75% (Abrahams and Burkitt 1970, Reyes et al 1993, Gustafsson and Tibbling 1994.…”
mentioning
confidence: 83%
“…Primary aspiration is commonly seen in infants and children with feeding and swallowing problems associated with neurological disease, anatomical anomalies and other aetiologies (Weiss 1988;Arvedson 1994;Colombo 1999). Short term manifestations of pulmonary aspiration are cough, wheeze, increased number and prolonged respiratory infections and atelectasis (Colombo 1999;Loughlin 1994).…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…Fluid consistencies are the most commonly aspirated material in people with swallowing dysfunction (Arvedson 1994;Rogers 1994;Taniguchi 1994;Morton 1999;Friedman 2000;Lefton-Greif 2000). In the case of thin fluids, texture restriction may entail eliminating the thin fluids from a person's diet and allowing thickened fluids to be orally consumed (Logemann 1983;Newman 2000).…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…(Reilly, Skuse & Poblette 1996;Reyes et al1993;Gisel & Patrick 1988). In some cases oral feeding is considered unsafe, due to high rates of oral aspiration (ie food and secretions are transported into the airway), with implications for the child's respiratory health, including the risk of chest infections and aspiration pneumonia (Rogers et al 1994).…”
Section: Introductionmentioning
confidence: 99%